Emergency Response for Architectural Heritage in Seismic Areas: An Integrated Approach to Safety and Conservation - Lia Ferrari (Heritage)
In 2015, hazard mitigation became a top priority on the international agenda, according to the United Nations Office for Disaster Risk Reduction. When it comes to architectural heritage, it is crucial to develop tools and site-specific response plans that can help the prompt and effective management of seismic events. The paper presents part of a research study carried out at the University of Parma, aimed at improving emergency strategies for the protection of cultural heritage damaged by earthquakes. Specifically, it analyses first aid and recovery reinforcements, with a specific focus on masonry churches affected by the 2012 quake in the Emilia Romagna region (Italy). The study highlights criticalities and good practices of a site-specific response. It shows that recovery with a sharp separation between emergency and reconstruction activities leads to wasted resources in terms of cost, material, and time. On the other hand, the most effective strategies for the conservation of architectural heritage in earthquake-prone areas have proved to be based on an integrated and shared approach, aimed at balancing safety, conservation, and economic issues. This leads to a broadening of the concept of emergency interventions and, more generally, of structural reinforcement in the field of architectural conservation.